Dynamic Behavior of Self-Piercing Riveted and Mechanical Clinched Joints of Dissimilar Materials: An Experimental Comparative Investigation - Yulong Ge; Yong Xia (Advances in Materials Science and Engineering)
The present work compares the dynamic effect of a self-piercing riveted (SPR) joint with that of a mechanical clinched joint having the dissimilar materials combination. The substrates used in this investigation are aluminum alloy AA5182-O and deep drawing steel DX51D+Z. The static and dynamic behaviors and the failure modes of the SPR and clinching joints are characterized by lap-shear, cross-tension, and coach-peel tests. The influence of the strain-rate-dependent mechanical behavior of the substrates on the joints is examined; this can help improve prediction of the energy absorption of the joints under impact loading. Considering the realistic baking process in a painting shop, the deforming and hardening effects on the SPR and the clinched joints induced by baking are also studied. The specimens are heated to 180°C for 30 min in an oven and then cooled down in air. The SPR and the clinched joints before and after the baking process are compared in terms of the mechanical behavior.